A Comparative Experimental Study on the Flexural Behavior of Geopolymer Concrete Beams Reinforced with FRP Bars - Sanaz Moazzenchi; Asghar Vatani Oskouei (Journal of Rehabilitation in Civil Engineering)
An environmentally friendly building system with suitable properties including durability can be made by using geopolymer concrete and FRP bars. The flexural behavior of geopolymer concrete beams made from Iran mines soil and reinforced with FRP and steel bars was examined in this work. In terms of reinforcement and concrete, the findings of the experimental investigation of geopolymer concrete beams were compared to those of standard cement concrete beams. To accomplish this purpose, a four-point flexural test was performed on 24 specimens of geopolymer and cement concrete beams reinforced with steel, GFRP, and CFRP bars. The initial cracking load, ultimate load, failure modes, number and width of cracks, load-deflection behavior, crack pattern, strain distribution, effective moment of inertia, and ductility were all investigated. The failure modes of tested beams were approximately similar to those predicted by codes, and a comparison of experimental findings with codes predictions reveals that these codes underestimated the beams' flexural strength, but ACI predictions are almost 20% more accurate than CSA ones. Geopolymer beams reinforced with FRP rebars and made with Iran mine soil showed similar results to reinforced cement beams, and the ductility ratio of FRP and steel reinforced geopolymer beams is 5% and 34% greater than that of reinforced OPC concrete, respectively.